Innovation in Agri-food Clusters Theory and Case Studies - Phillips, Peter W.B (CABI, 2014)
This monograph is the result of 10 years of on-going research undertaken as part of the Innovation Systems Research Network (ISRN), a major collaborative research initiative funded by the Social Science and Humanities Research Council of Canada. In one way, our experience with this work reiﬁ es the serendipitous nature of innovation. Each of us engaged in this research more by chance than by design, and our success was due to open collaboration. Phillips was the Van Vliet Chair Professor in Agricultural Economics at the University of Saskatchewan in 1999 when Marlene Moleski, a colleague with the Canadian Department of Western Diversiﬁ cation, passed his name along to Adam Holbrook, Associate Director of CPROST at Simon Fraser University and an instigator of INNOCOM, a precursor research network to the ISRN. Phillips then made a presentation at a Policy Research Initiative conference in Ottawa; David Wolfe and Meric Gertler, the Principal Investigators on ISRN, were in the audience. Based on those meetings, Phillips was enrolled as a collaborator in the project and has stayed with it as he moved from Agricultural Economics through Political Studies to the Johnson-Shoyama Graduate School of Public Policy at the University of Saskatchewan.